Pengembangan Media Pembelajaran Berbasis Google Sites pada Materi Perawatan Sistem EFI untuk Siswa Kelas XI TKRO di SMK Negeri 1 Padang - Soni Afrizal; Andrizal Andrizal; Hasan Maksum; Rifdarmon Rifdarmon (International Forum of Researchers and Lecturers, 2026)
This study aims to develop Google Site-based learning media on Electronic Fuel Injection (EFI) System Maintenance material for class XI students of Automotive Light Vehicle Engineering (TKRO) at SMK Negeri 1 Padang. The background of this study is based on the problems of learning that is still monotonous, less than optimal use of digital technology in the teaching and learning process, and low motivation and independence of student learning. This study uses the Research and Development (R&D) method with a 4-D development model that includes the Define, Design, Develop, and Disseminate stages. The research subjects consisted of two experts, namely media experts and material experts, two subject teachers, and 31 class XI TKRO students. Data collection techniques were carried out through validation questionnaires and practicality questionnaires. The results of the study showed that Google Site-based learning media has a very high level of validity based on the assessment of media experts by 93.33% and material experts by 90.00%. In addition, this media was considered very practical by teachers with a percentage of 94.25% and practical by students with a percentage of 78.2%. Thus, Google Site-based learning media is declared suitable for use as a learning tool to increase learning motivation, student independence, and learning effectiveness in the EFI System Maintenance material in vocational schools.